THE EFFECT OF LIVING CIRCUMSTANCE ON CHARACTERS (HEATHCLIFF, CATHERINE AND YOUNG CATHERINE) IN WUTHERING HEIGHTS BY EMILY BRONTE = SỰ ẢNH HƯỞNG CỦA MÔI TRƯỜNG SỐNG TỚI NHÂN VẬT (HEATHCLIFF, CATHERINE VÀ YOUNG CATHERINE) TRONG TÁC PHẨM WUTHERING HEIGHTS CỦA EMILY BRONTE - Phạm, Thị Lụa (2020)
Wuthering Heights is the only novel of Emily Bronte, published in 1847. The novel remarks one of the great contributions to the English literature from female author so it calls the public’s attention to various aspects from detail to general. With its popularity and values in terms of literature, the novel became a significance subject for researchers and scholars to study. The researcher took a decision to investigate “the effect of living circumstance on characters (Heathcliff, Catherine and young Catherine) in Wuthering Heights”. It is considered a new and practical thesis for study because its aim is to discover and analyze the contribution of living circumstance on characters. First, the background for the study will be provided with some terms related to living circumstance, novel as well as information of the author Emily Bronte and Wuthering Heights particularly. Secondly, the next part will be a development of the contribution of living circumstance on some protagonists of Wuthering Heights based on the terms mentioned before. Finally, the researcher will summarize the outcomes and give out some limitations of the study together with suggestions for further studies.